The Effectiveness of Learning Listening Using e-Belajar Kota Banda Aceh - Khazinat Khazinat; Zaiyana Putri; Sabrina Sabrina (International Conference on Multidisciplinary Research, 2022)
Language is a basic tool of human communication, and listening is one of the four important language skills that allow a person to receive, comprehend, and react to a certain piece of information accordingly. Various multimedia applications have been created to improve students’ English listening skill, such as eBelajar Kota Banda Aceh. However, little is known about the perceptions of students regarding the effectiveness of eBelajar in improving students’ listening skill and the obstacle they face when using this application. Thus, this research attempted to investigate these issues. Seventy-six students were involved as research participants, consisting of 33 female students and 43 male students, selected through a random sampling technique. The data were collected using questionnaires and analyzed using the percentage formula. The results showed that the students perceive eBelajar Kota Banda Aceh as an effective platform to learn English listening skill, but it occasionally presents a challenge for the students when using it, which is its high dependency on the internet connection and speed. Keywords: Ebelajar, Learning English, Listening Skill, Kota Banda Aceh